PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP PENJUALAN DI INDORIVA ONLINE PADA PT. MULTISUKSES ENERGI - Nidia Darma Putri; Maizul Rahmizal (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The purpose of this study was to examine the effect of product quality, price and promotion variables on sales in Indoriva Online at PT. Multisukses Energi. Collecting data by distributing questionnaires to 86 respondents using a non-probability sampling technique, that is, part of the population is sampled, using multiple linear regression with the help of SPSS. The method used in this study using quantitative methods, namely multiple linear regression on product quality, price and promotion. The types and sources of data used in this study are primary data. From the results of the analysis of product quality, price and promotion obtained a significant value of t count > from t table, then the hypothesis in this study is declared accepted. Based on the results obtained, it can be concluded that product quality, price and promotion have a positive and significant effect on sales